Biweekly sunitinib regimen reduces toxicity and retains efficacy in metastatic renal cell carcinoma: A single‐center experience with 31 patients. (1st November 2012) - Neri, Bruno; Vannini, Agnese; Brugia, Marco; Muto, Andrea; Rangan, Sheila; Rediti, Mattia; Tassi, Renato; Cerullo, Carmine
<x xml:space="preserve">Abstract</x> Objectives Sunitinib is the standard care for first‐line treatment of metastatic renal cell carcinoma. The aim of this study was to determine whether a sunitinib regimen of 50 mg/day 2‐weeks on/1‐week off could maintain the same dose‐intensity as the standard 4‐weeks on/2‐weeks off schedule, and provide the same efficacy in terms of objective response, progression‐free survival and overall survival, while reducing drug‐related toxicity. Methods A total of 31 patients with metastatic renal cell carcinoma received sunitinib orally at the dose of 50 mg/day in a 2‐weeks on/1‐week off regimen until disease progression or intolerable toxicities occurred. Results All enrolled patients were assessable in terms of toxicity and response. They received treatment for a median of 16 months (range 2.0–36.0+ months). A total of 13 patients (42%) obtained an objective response; disease stabilization was achieved in 10 patients (32%), whereas eight patients (26%) experienced disease progression. The most important toxicities were anemia, gastrointestinal effects, fatigue and hypertension, but they were all controlled. Conclusions Sunitinib 50 mg given orally in a 2‐weeks on/1‐week off regimen can provide a high response rate and avoid drug‐related toxicities, achieving the same dose intensity as the standard schedule, and probably longer disease control.